2009
DOI: 10.1007/s00467-008-1083-8
|View full text |Cite
|
Sign up to set email alerts
|

Continuous venovenous hemodiafiltration trace element clearance in pediatric patients: a case series

Abstract: Continuous renal replacement therapy (CRRT) is used to treat critically ill children with acute kidney injury. The effect of CRRT on trace element clearance is poorly characterized. The purpose of this study was to quantify the transmembrane clearance of chromium, copper, manganese, selenium and zinc during continuous venovenous hemodiafiltration (CVVHDF). The transmembrane clearance of trace elements was assessed prospectively in five critically ill children receiving CVVHDF at the pediatric intensive care un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 28 publications
1
30
2
Order By: Relevance
“…CRRT removes waste products, but also medications and nutrients [8,9] through the processes of filtration and dialysis [9]. Limited data are available concerning CRRT-induced loss of nutritional substrates, vitamins, and trace elements [10,11]. Losses of trace elements are likely to occur because they are small in size and thus dialyze readily [9].…”
Section: Introductionmentioning
confidence: 99%
“…CRRT removes waste products, but also medications and nutrients [8,9] through the processes of filtration and dialysis [9]. Limited data are available concerning CRRT-induced loss of nutritional substrates, vitamins, and trace elements [10,11]. Losses of trace elements are likely to occur because they are small in size and thus dialyze readily [9].…”
Section: Introductionmentioning
confidence: 99%
“…Based on folate levels in the patients of the Tapy et al study [54], it is possible that additional folate supplementation is needed in children who are receiving CRRT for prolonged periods. It has been suggested that the recommended daily allowances should be provided and that watersoluble vitamin, trace element and folate levels be strictly monitored in children receiving prolonged RRT [57,69].…”
Section: Vitamins and Trace Elementsmentioning
confidence: 99%
“…Increased protein provision is likely necessary for neonatal ECLS patients if CRRT is utilized. Other CRRT‐mediated losses may occur, including the loss of trace minerals, key nutrients, and water‐soluble vitamins, and the clinical significance of these losses remains unknown . Guidelines for PN provision exist for adult patients with renal failure and include recommendations regarding supplementation when CRRT is utilized; however, no such guidelines exist for neonates .…”
Section: Complications and Concurrent Therapiesmentioning
confidence: 99%